2014
DOI: 10.1194/jlr.r048090
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal storage diseases and the heat shock response: convergences and therapeutic opportunities

Abstract: The lysosomal storage diseases (LSDs) describe a heterogenous family of rare inherited diseases caused by mutations in lysosomal proteins and are characterized by accumulation of macromolecules or monomeric compounds inside organelles of the endo-lysosomal system ( 1-3 ). The LSDs present complex disease phenotypes with the mechanisms leading to pathology being poorly understood, as the disease and extent of pathology seem to depend on the spatiotemporal accumulation of substrates which have a variety of downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 178 publications
(189 reference statements)
1
45
0
Order By: Relevance
“…In addition, HSP70, known to be crucial in unlocking protein disaggregation (Nillegoda et al, 2015, Nillegoda and Bukau, 2015), was isolated as one of numerous GCase-associated proteins dependent on the presence of PGRN in our unbiased proteomic screen. Interestingly, the interaction between GCase and HSP70, as well as their involvement in GD, had been reported previously (Lu et al, 2011, Yang et al, 2014, Ingemann and Kirkegaard, 2014), although the nature of this association was unclear. In addition, the binding of PGRN to HSP70 was also independently reported (Almeida et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…In addition, HSP70, known to be crucial in unlocking protein disaggregation (Nillegoda et al, 2015, Nillegoda and Bukau, 2015), was isolated as one of numerous GCase-associated proteins dependent on the presence of PGRN in our unbiased proteomic screen. Interestingly, the interaction between GCase and HSP70, as well as their involvement in GD, had been reported previously (Lu et al, 2011, Yang et al, 2014, Ingemann and Kirkegaard, 2014), although the nature of this association was unclear. In addition, the binding of PGRN to HSP70 was also independently reported (Almeida et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…Arimoclomol amplifies the production of HSP70 family members which have been implicated in the proper folding and chaperoning of GCase as well as in maintenance of lysosomal integrity during cellular stress (Kirkegaard et al 2010;Kirkegaard et al 2016;Lu et al 2011;Yang et al 2014;Yang et al 2013;Yang et al 2015;Ingemann & Kirkegaard 2014;Mu et al 2008). Studies of the induction of HSPs by small molecules have until now made use of agents that provide proof-of-principle but due to their cytotoxic nature are not suited for development for chronic diseases (Mu et al 2008;Ingemann & Kirkegaard 2014;Kirkegaard 2013). These studies have however, revealed several HSP-dependent mechanisms regulating the processing of GCase.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the HSP70 family of molecular chaperones include HSP70 encoded by HSPA1A and BiP/GRP78/HSP70-5 encoded by HSPA5 (Daugaard et al 2007), which have been shown to be important for lysosomal and GCase function (Wang et al 2011;Kirkegaard et al 2016;Kirkegaard et al 2010;Ingemann & Kirkegaard 2014;Jian et al 2016). Studies of GCase, and its most prevalent missense mutations for nonneuronopatic (N370S) and neuronopathic (L444P) GD, have demonstrated that it binds to HSP70 and HSP90 which in concert with cochaperones such as TCP1 guide the enzyme through to either correct folding and lysosomal activity, or to the ubiquitin proteasome pathway for degradation (Lu et al 2011;Yang et al 2014;Yang et al 2015;Jian et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not yet been determined whether the proteasome activity plays a role in HSP expression. Recently, the Hsp70 has been shown to rescue the Niemann-Pick disease by stabilizing the lysosomes [50], thus suggesting that the potential therapeutic strategy of heat shock proteins for LSD treatment [51]. In the future, it will be worth addressing the influences of HSP expression and/or the heat shock responses on ERT potency/efficacy.…”
Section: Discussionmentioning
confidence: 99%